Ethnic Federalism and Political (in)Stability in Ethiopia: The Tigray Region Conflict (1991-2021) - Mengesha, Eba Gemechu (Daystar University, School Arts and Social Sciences, 2022)
This study sought to examine the link between ethnic federalism and political (in)stability in Ethiopia, particularly the Tigray Conflict. The study employed a case study approach to gain a better understanding of Ethiopia's political (in)stability and its relationship to ethnic federalism. The objectives of this study were to establish a link between ethnic federalism and political (in)stability in Ethiopia, explore the narratives behind Ethiopia's Tigray conflict; and examine the effects of implementing ethnic-based federalism in Ethiopia. Various excerpts from authors who are knowledgeable about ethnic federalism and political (in)stability in Ethiopia are included in the literature review for this research. The study used, the research methodology that directed the study's data collection, interpretation and analysis. The study employed the political theory of federalism as well as the classical theory of federalism, and their fundamental principles provided adequate explanation for an understanding of Ethiopia's federal system of government. More specifically, the study sought to comprehend the federal system and its potential role in the political instability that has emerged since Ethiopia became a federal state. Hence, the study demonstrates that Ethiopian federalism was founded on ethnicity, and that this did not alleviate the country's pre-existing tensions. Moreover, the study revealed that the Tigray conflict was merely politically motivated and orchestrated by political elites when the central government criminalized the TPLF in the Tigray region. The findings shows that ethnic federalism has not reduced conflict but has instead heightened rivalry between groups competing for control of natural resources as well as administrative boundaries and has failed to end long-standing ethnic based conflicts and the pursuit of an equitable distribution of power and resources. On the contrary, it is noted that the federal system is/was not a source of conflict, but rather benefited the majority of ethnic groups who had previously been marginalized from central authority and granted them self-rule. However, ethnic politicization remains a problem in Ethiopia, jeopardizing national security and unity.
Thesis Abstract
Keywords: ethnic federalism; political (in)stability